Benedek László ideggyógyász-professzor, a debreceni m. kir. Tisza István-Tudományegyetem 1935–36. tanévi rector magnificusa - Mudrák, József (Gerundium, 2019)
László Benedek Professor of the Neurology, the Rector Magnificus of the Hungarian Royal István Tisza University of Debrecen during the academic year 1935/1936. The first professor of neurology and psychiatry and the director of the Department of Neurology of the University of Debrecen between 1921 and 1936 was László Benedek who studied at Cluj as a student of Károly Lechner. In the academic year of 1935/36 he held the post of the Rector of the university. This period was the era of silent development in the life of the university. Benedek as Rector focused on improving the living circumstances of the students. After his rectorate he was appointed to a professorship of the Péter Pázmány University of Arts and Sciences and the director of the Clinic of Neurology and Psychiatry in Budapest. His wife was the wellknown actress Irén Zilahy. After her tragic death in April 1944 Benedek collapsed and in March 1945 he committed suicide in Kitzbühel in Austria. László Benedek was a brilliant lecturer, an urging leader, and an inventive professor of science whose work in several partial branches of science was outstanding.